Steady state and transient simulation for electricity‐gas integrated energy systems by using convex optimisation. Issue 9 (16th March 2018) - Chen, Sheng; Wei, Zhinong; Sun, Guoqiang; Wang, Dan; Zang, Haixiang
Abstract : The increasing interdependence between electric power and natural‐gas systems requires integrated simulation tools applicable to the coupled system. Therefore, this study proposes steady‐state and transient simulation tools for electricity‐gas integrated energy systems (IESs) by using convex optimisation. Steady‐state IES simulation is designed for long‐term planning studies while transient IES simulation, which includes line‐pack storage, is designed for real‐time operational research. The proposed convex steady‐state gas flow model introduces binary variables to represent gas flow directions, and employs the second‐order cone (SOC) to relax non‐convex pipeline gas flow equations. As a result, steady‐state gas flow analysis is formulated as a mixed integer SOC programming problem. The proposed transient gas flow model employs the implicit finite difference method to transform partial differential equations into algebraic difference equations. Moreover, the short‐term gas flow directions are specified and SOC relaxations are used. Simulation results on an integrated IEEE 24‐node system and Belgian 20‐node gas system verify the effectiveness of the proposed SOC models. The impacts of wind power forecast errors on multi‐period gas network operations are also investigated.